Epigenetic silencing of DKK3 in medulloblastoma - Valdora, Francesca; Banelli, Barbara; Stigliani, Sara; Pfister, Stefan; Moretti, Stefano; Kool, Marcel; Remke, Marc; Bai, Alfa H. C.; Brigati, Claudio; Hielscher, Thomas; Romani, Massimo; Servidei, Tiziana; et al. (International journal of molecular sciences, 2013)
Medulloblastoma (MB) is a malignant pediatric brain tumor arising in the cerebellum consisting of four distinct subgroups: WNT, SHH, Group 3 and Group 4, which exhibit different molecular phenotypes. We studied the expression of Dickkopf (DKK) 1-4 family genes, inhibitors of the Wnt signaling cascade, in MB by screening 355 expression profiles derived from four independent datasets. Upregulation of DKK1, DKK2 and DKK4 mRNA was observed in the WNT subgroup, whereas DKK3 was downregulated in 80% MBs across subgroups with respect to the normal cerebellum (p < 0.001). Since copy number aberrations targeting the DKK3 locus (11p15.3) are rare events, we hypothesized that epigenetic factors could play a role in DKK3 regulation. Accordingly, we studied 77 miRNAs predicting to repress DKK3; however, no significant inverse correlation between miRNA/mRNA expression was observed. Moreover, the low methylation levels in the DKK3 promoters (median: 3%, 5% and 5% for promoter 1, 2 and 3, respectively) excluded the downregulation of gene expression by methylation. On the other hand, the treatment of MB cells with Trichostatin A (TSA), a potent inhibitor of histone deacetylases (HDAC), was able to restore both DKK3 mRNA and protein. In conclusion, DKK3 downregulation across all MB subgroups may be due to epigenetic mechanisms, in particular, through chromatin condensation.